Effects of mitotane on gene expression in the adrenocortical cell line NCI-H295R: a microarray study. (September 2012) - Zsippai, Adrienn; Szabó, Diana Rita; Tömböl, Zsófia; Szabó, Peter M; Éder, Katalin; Pállinger, Éva; Gaillard, Rolf C; Patócs, Attila; Tóth, Sára; Falus, András; Rácz, Károly; Igaz, Peter
Aim: The adrenolytic agent mitotane is widely used in the treatment of adrenocortical cancer; however, its mechanism of action is poorly elucidated. We have studied mitotane-induced mRNA expression changes in the NCI-H295R adrenocortical cancer cell line.Materials & methods: Cell viability and hormone assays were used to select the optimal mitotane concentration effectively inhibiting hormone secretion without affecting cell viability. RNA isolated from cultures treated for 48 and 72 h was subjected to Agilent 4×44K microarray platforms. Microarray results were validated by quantitative reverse-transcription PCR.Results: Altogether, 117 significantly differentially expressed genes were detected at 48 h and 72 h (p < 0.05) in mitotane-treated samples relative to controls. Three significantly underexpressed genes involved in steroid hormone biosynthesis ( HSD3B1, HSD3B2 and CYP21A2 ) and four significantly overexpressed genes ( GDF15, ALDH1L2, TRIB3 and SERPINE2 ) have been validated.Conclusion: Gene-expression changes might be involved in the adrenal action of mitotane and in the inhibition of hormone secretion. Original submitted 20 January 2012; Revision submitted 17 May 2012